Preparation of Cadmium Nanoparticles by Laser Ablation Method in Water at Different Energies and Their Biological Application - M. Awad, Wildan; A. Kareem, Nada (Al-Nahrain Journal of Science, 2025)
This work includes preparation of CdO nanoparticles by laser ablation in water at two energies (360 mJ and 560 mJ).  Various techniques (XRD, SEM, and AFM) were employed to ascertain the structural and morphological properties. X-ray diffraction of CdO films at different energies (360 mJ and 560 mJ) demonstrated their polycrystalline nature with a cubic phase. The crystalline size was 28.30 and 40.16 nm at energies 360 mJ and 560 mJ respectively. AFM measurements indicate that the average diameter has risen from 82.99 nm to 117 nm, while the surface roughness has escalated from 1.18 nm to 2.68 nm as laser energy rose from 360 mJ to 560 mJ. The SEM scans indicate that the substrate surfaces are uniformly coated with interconnected particles, exhibiting smallest diameter 13.94 nm and 21.78 nm at energies of 360 mJ and 560 mJ, respectively. (UV, and FTIR) techniques were employed to ascertain the optical and chemical properties, where the energy bandgap for CdO is documented as 3.8 eV and 3.6 eV at energies 360 mJ and 560 mJ respectively. FTIR spectra identified the range 400-1000 cm-1 as the characteristic bands for the CdO mode at 400-1000 cm-1.  Increased inhibition of bacteria and fungi was observed with increasing laser energy concentration, where the inhibition zone of Staphylococcus aureus and candida albicans was 12 mm and 19 mm at 360 mJ, while it records 14 mm and 20 mm at 560 mJ.